Handbook of Good Psychiatric Management for Adolescents With Borderline Personality Disorder - Choi-Kain, Lois W. (American Psychiatric Association Publishing, 2021)
This manual demystifies borderline personality disorder in young people by using the principles of good psychiatric management (GPM) to offer clinicians essential guidelines for generalist care. The authors outline common problems that arise during each phase or aspect of treatment, from diagnosis and pharmacology to family interventions, and discuss how to address them.